Suppression of CFTR premature termination codons and rescue of CFTR protein and function by the synthetic aminoglycoside NB54 - Rowe, Steven M. (2011)
Certain aminoglycosides are capable of inducing “translational readthrough” of premature termination codons (PTCs). However, toxicity and relative lack of efficacy deter treatment with clinically available aminoglycosides for genetic diseases caused by PTCs, including cystic fibrosis (CF). Using a structure-based approach, the novel aminoglycoside NB54 was developed that exhibits reduced toxicity and enhanced suppression of PTCs in cell-based reporter assays relative to gentamicin. We examined whether NB54 administration rescued CFTR protein and function in clinically relevant CF models. In a fluorescence-based halide efflux assay, NB54 partially restored halide efflux in a CF bronchial epithelial cell line (CFTR genotype W1282X/F508del), but not in a CF epithelial cell line lacking a PTC (F508del/F508del). In polarized airway epithelial cells expressing either a CFTR-W1282X or -G542X cDNA, treatment with NB54 increased stimulated short-circuit current (I(SC)) with greater efficiency than gentamicin. NB54 and gentamicin induced comparable increases in forskolin-stimulated I(SC) in primary airway epithelial cells derived from a G542X/F508del CF donor. Systemic administration of NB54 to Cftr−/− mice expressing a human CFTR-G542X transgene restored 15–17% of the average stimulated transepithelial chloride currents observed in wild-type (Cftr+/+) mice, comparable to gentamicin. NB54 exhibited reduced cellular toxicity in vitro and was tolerated at higher concentrations than gentamicin in vivo. These results provide evidence that synthetic aminoglycosides are capable of PTC suppression in relevant human CF cells and a CF animal model and support further development of these compounds as a treatment modality for genetic diseases caused by PTCs.